DNA Damage, Repair, and Cancer Metabolism - Turgeon, Marc-Olivier; Perry, Nicholas J. S.; Poulogiannis, George (Frontiers in Oncology, 2018)
Although there has been a renewed interest in the field of cancer metabolism in the last decade, the link between metabolism and DNA damage/DNA repair in cancer has yet to be appreciably explored. In this review, we examine the evidence connecting DNA damage and repair mechanisms with cell metabolism through three principal links. (1) Regulation of methyl- and acetyl-group donors through different metabolic pathways can impact DNA folding and remodeling, an essential part of accurate double strand break (DSB) repair. (2) Glutamine, aspartate, and other nutrients are essential for de novo nucleotide synthesis which dictates the availability of the nucleotide pool, therefore influencing DNA repair and replication. (3) Reactive oxygen species (ROS), which can increase oxidative DNA damage and hence the load of the DNA-repair machinery, are regulated through different metabolic pathways. Interestingly, while metabolism affects DNA repair, DNA damage can also induce metabolic rewiring. Activation of the DNA damage response (DDR) triggers an increase in nucleotide synthesis and anabolic glucose metabolism, while also reducing glutamine anaplerosis. Furthermore, mutations in genes involved in the DDR and DNA repair also lead to metabolic rewiring. There is an increasing amount of research working to unfold the links between cancer metabolism and DNA damage/DNA repair opening up opportunities to investigate the mechanistic basis underlying potential metabolic vulnerabilities of a substantial fraction of tumors.